The new institutional approach to solving dilemmas of collective action - Бульдович, П. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article analyzes the problems of collective action and possible solutions within the new institutional approach. The author examines the most popular dilemmas in which rational individual behavior causes irrational collective result. The article also attempts to demonstrate how the new institutionalism analytical tools can be used to study echanisms which are able to overcome the inefficiencies of collective action, bypassing the typical way to solve this problem - state paternalism and market mechanisms.